Occurrence and Molecular Characterization of Abundant tet(X) Variants Among Diverse Bacterial Species of Chicken Origin in Jiangsu, China - Li, Yingshan; Peng, Kai; Yin, Yi; Sun, Xinran; Zhang, Wenhui; Li, Ruichao; Wang, Zhiqiang (Frontiers in Microbiology, 2021)
Many novel tigecycline inactive enzymes encoded by tet(X) variants from different bacteria were discovered since the plasmid-mediated tet(X3) and tet(X4) genes conferring high-level resistance to tigecycline in Enterobacterales and Acinetobacter were reported. However, there have been no comprehensive studies of the prevalence of different tet(X) variants in poultry farms. In this study, we collected 45 chicken faeces samples, isolated tet(X) positive strains and performed antimicrobial susceptibility testing, conjugation assay, whole genome sequencing and bioinformatics analysis. A total of 15 tet(X)-bearing strains were isolated from 13 samples. Species identification and tet(X) subtyping analysis found that the 15 strains belonged to eight different species and harbored four different tet(X) variants. Genomic investigation showed that transmission of tet(X) variants was associated with various mobile genetic elements, and tet(X4) was the most prevalent mediated by conjugative plasmids. Meanwhile, we firstly characterized a plasmid coharboring tet(X6) and blaOXA-58 in Acinetobacter baumannii. In summary, we demonstrated that different tet(X) variants were seriously disseminated in chicken farming environment and dominated by tet(X4). This finding expands the understanding of the prevalence of tet(X) among different animal sources, and it was advocated to reduce the usage of antibiotics to limit the emergence and transmission of novel tet(X) varaint in the poultry industry.